Neonatal pain: literature review from 1998 to 2008 - Maria Cristina Pauli da Rocha; Lisabelle Mariano Rossato (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Literature review related to neonatal pain. Objectives: to identify scientific articles related to the theme in computerized database - Medline, Lilacs and Cinahl; to identify themes related to neonatal pain. The methodology utilizes research computer and/or manual bibliography. Data were obtained from 32 scientific literatures from 1998 to 2008. Results: studies were published mainly in English. Five themes were identified: painful stimulation to neonates; expression of neonatal pain; assessment instruments of neonatal pain; methods for control and relief of neonatal pain; perception, assessment and management of neonatal pain. Conclusion: the reports revealed gap in care such as wrong methods of pain evaluation and management, inconsistent documentation, absence of written rules leading to sub or mistreatment. Although instruments of pain assessment in neonates are being clinically tested by several researchers, there is a deficiency of published studies (such as nurses experience reports in the use of such tools) in clinical practice in the daily life of neonatal intensive care unit.